Analisa pemilihan Terapi Kombinasi Metformin dengan Penambahan Satu Obat Sulfonylurea pada Pasien Diabetes Melitus Tipe 2 Studi Cross Sectional - , OKTAVIAN RIZKI ILAHI; , Prof. dr.Iwan Dwiprahasto, M.Med. Sc. Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Diabetes mellitus type 2 is a metabolic syndrome characterized by hyperglycemia. Management of this disease is consists of lifestyle modification and administration of pharmacologic agent for lifetime to reach normal blood glucose levels, thus preventing disease complications occur. The prevalence in the world is 2.8%, while in Indonesia was 5.7% in urban areas. The first line pharmacotherapy of diabetes mellitus is metformin monotherapy, if monotherapy cannot reach normal blood glucose levels, it will switch to metformin dual therapy which is added by whether sulfonylureas, DPP-4 inhibitors, GLP-1 receptor antagonists, or basal insulin. Sulfonylurea is the best option of antidiabetic drug added to dual therapy in lowering blood glucose levels, but because of difference in efficacy among sulfonylurea types, it is needed evidence-based medicine research to determine which one is the best option with the most efficient price. Objective: To compare the effectiveness of three type of metformin dual therapy with the addition of sulfonylurea in declining fasting blood glucose levels in type 2 diabetes mellitus patients and compare the average price of each type of drug therapy group. Research Methods:The study on 15,200 patients visits by medical record of 8 health clinic owned by oil companies in borneo during 5 years from 2005 - 2009. Subject criteria were type 2 diabetes mellitus patients who received metformin dual therapy with sulfonylurea and have suitable fasting blood glucose laboratory results. Data were processed using oneway ANOVA between therapy group and fasting blood glucose laboratory results. Besides hypothesis analysis data were processed to determine descriptive analysis about the distribution of prescription in three treatment groups, duration of treatment, sex, comorbid diseases, and treatment costs. Results:There were 79 prescriptions which have suitable inclusion and exclusion criterias. Data were analyzed using oneway ANOVA in mean fasting blood glucose among three treatment groups, metformin + glibenclamide (204 mg/dl ± 58), metformin + glicazide (172 mg/dl ± 67), and metformin + glimepiride (164 mg/dl ± 49). After a posthoc oneway ANOVA analysis in fasting blood glucose only metformin + glimepiride have significant value in declining fasting blood glucose level better than metformin + glibenclamide (-40 mg/dl ± 19, P<0,05). Average price among treatment groups were processed by descriptive analysis, and the results are metformin + glibenclamide Rp 3814 ± 131.73